PENGARUH EMOSI POSITIF DAN EKUITAS MEREK TERHADAP PEMBELIAN IMPULSIF WANITA - Putri, Moudy Nitazya Dwi; Juwitaningrum, Ita; Wyandini, Diah Zaleha (JURNAL PSIKOLOGI INSIGHT, 2019)
This study aimed to determine the effect of positive emotions and brand equity on impulsive buying on female consumers. The research used the quantitative method with 414 female consumers. The instruments were the Dispositional Positive Emotion Scale, Brand Equity Scale, and The Impulse Buying Tendency Scale. The data analysis techniques which is used in this research is multiple regression. The results show that positive emotions had no effect on impulsive buying. Furthermore this study also show that brand equity has a direct effect on impulsive buying